The last battle - Lewis, C.S. (Clive Staples), 1898-1963; Bayne, Pauline, ill. (New York Harper Collins Pub., 1984)
When evil comes to Narnia, Jill and Eustace help fight the great last battle and Aslan leads his people to a glorious new paradise
Keywords: Fantasy